(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2014)
The patient, a young soldier aged 36 years having past history of malaria, was admitted in CMH Dhaka on 17 August 2011 as a transferred case from CMH Saidpur and died on 22 August 2011. The deceased was admitted in CMH Saidpur on 05 August 2011 with high fever for 05 days along with generalized joint and muscle pain. In spite of all available treatment the patient was deteriorating and he was then transferred to CMH Dhaka. At that time the patient was febrile, dehydrated and toxic with lymphadenopathy, extremely tender joints and muscles. The patient rapidly developed acute kidney failure and gradually developed features of DIC. His bone marrow examination revealed dyserythropoiesis with predominantly eosinophilic granulopoiesis, suggestive of myeloproliferative neoplasm with prominent eosinophilia. The patient was treated with injectable antibiotics, antimalarial and oral prednisolone with all intensive care facilities. Ultimately all attempts were proved unsuccessful and he died on 22 August 2011 at 1700 hrs. On autopsy the deceased had intra atrial thrombus and possibly that was the immediate cause of death. A haematological malignancy, myeloproliferative neoplasm with prominent eosinophilia, can very well produce such a fatal condition. DOI: http://dx.doi.org/10.3329/jbcps.v31i3.20985 J Bangladesh Coll Phys Surg 2013; 31: 162-167